Utjecaj tekstova latinskih rimskih sakramentara na crkvenoslavensku rimsku liturgiju (9. - 14. stoljeće) - Kuhar, Kristijan (Array, 2019)
The liturgical texts of the Church Slavonic sacramentaries (Kiev Leaflets, Vienna Leaflets, Sinai missal Sin. Slav. 5N and others) from the early stages of the Slavic liturgy (9th to 14th century) with its textological and euchological content mostly belong to the Roman rite. These texts are euchological texts with proper liturgical function: texts are written and arranged for the celebration of the Mass and they are preserved in the liturgical book called sacramentary. The medieval Latin liturgical textological tradition is divided into two branches: Gelasian and Gregorian, which formed a unique textological tradition in parts of Northern Italy and Transalpine countries (from Aquileia to Salzburg) establishing a new textological tradition known as the »Gelasianized-Gregorian Sacramentary«, which was used in the mentioned parts of Central Europe. Based on the research of the history of Old Church Slavonic liturgy and historical and comparative analysis of Latin and Church Slavonic texts, mostly conducted for the doctoral thesis entitled Historical and liturgical peculiarities of the early stages of the Slavonic liturgy, this study presents influences of Latin liturgical textological tradition from Central Europe on the oldest Church Slavonic translations of sacramentaries from 9th to 14th century and other liturgical texts, mainly euchological, which continued to exist in the Croatian Glagolitic tradition even after the liturgical reform at the end of the 13th century.